Clinical Implication of Heart Rate Variability in Obstructive Sleep Apnea Syndrome Patients. Issue 5 (July 2015) - Kim, Yoo Suk; Kim, Sung Yul; Park, Do Yang; Wu, Hee Won; Hwang, Gyo-Seung; Kim, Hyun Jun
<x xml:space="preserve">Abstract</x> Abstract Obstructive sleep apnea syndrome (OSAS) is a common disease with the prevalence of approximately 10% in general population, and this disease entity is considered to be highly related with the development of cerebrovascular and cardiovascular diseases. In the pathogenesis of cardiovascular disease, maintaining the homeostasis of autonomic nervous system (ANS) is critical. To evaluate the homeostasis of ANS, heart rate variability (HRV) is commonly used. The object of this study was to evaluate the homeostasis of ANS using the parameters of HRV and to elucidate the correlation between the parameters and apnea-hypopnea index (AHI). Methods: Retrospective review of 806 patients was performed and 164 patients who were diagnosed as having OSAS by in-room polysomnography and met the criteria of age, sex, and body mass index were enrolled. The calculation of HRV parameters was executed using echocardiographic data from polysomnography. Results: Between the control group (N = 81, AHI < 5) and OSAS patient group (N = 83, AHI > 15), standard deviation of NN (SDNN) intervals, SDNN index, HRV triangular index, very low frequency (VLF), low frequency (LF), 5-minute total power (TP), and low-frequency to high-frequency (LF/HF) ratio showed significant differences. In the correlation analysis between AHI and HRV parameters, only LF/HF ratio was proven to be significant. Conclusions: Elucidating the imbalance of ANS in OSAS patients was feasible by HRV and its parameters.